2007
DOI: 10.1177/0091270007299431
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, Tolerability, and Safety of ACP‐103 Following Single or Multiple Oral Dose Administration in Healthy Volunteers

Abstract: The pharmacokinetics, safety, and tolerability of ACP-103, a selective serotonin 5-HT(2A) receptor inverse agonist, were evaluated in 2 double-blind, placebo-controlled, dose escalation studies in healthy male volunteers. Pharmacokinetic sampling was measured up to 216 hours after single oral/nasogastric doses of ACP-103 and after the last dose of once-daily oral administration of ACP-103 for 14 days. Single doses of ACP-103 (20-300 mg) resulted in dose-proportionate mean C(max) values (9-152 ng/mL) and AUC(0-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 10 publications
5
44
0
2
Order By: Relevance
“…Initial clinical studies in normal healthy volunteers showed that pimavanserin was well tolerated in humans both when given acutely and subchronically [38]. Nausea and vomiting were considered to be dose-limiting following 14 days of once daily oral dosing at 150 mg; 100 mg QD of pimavanserin given over the same period was therefore estimated to be the maximum tolerated dose.…”
Section: Clinical Studies With Pimavanserinmentioning
confidence: 99%
“…Initial clinical studies in normal healthy volunteers showed that pimavanserin was well tolerated in humans both when given acutely and subchronically [38]. Nausea and vomiting were considered to be dose-limiting following 14 days of once daily oral dosing at 150 mg; 100 mg QD of pimavanserin given over the same period was therefore estimated to be the maximum tolerated dose.…”
Section: Clinical Studies With Pimavanserinmentioning
confidence: 99%
“…Indeed, newer highly selective 5-HT 2A receptor antagonists, like M100907 (volinanserin), ACP-103 (primavanserin), and SR46349B (eplivanserin), are currently in clinical trials as novel therapeutics to treat insomnia [68] and there are no reports in literature describing effects on hypertension, inflammation, or other cardiovascular processes. One report, however, examining the physiological and pharmacokinetics of ACP-103 in a small study comprised of normal human subjects has been published that concluded that there were no significant changes in vital signs or ECG associated with treatment for up to fourteen days [69]. …”
mentioning
confidence: 99%
“…Preliminary studies assessing adverse effects and bioavailability in healthy controls suggested minimal issues with tolerability and long half life of pimavanserin 20-50 mg without interference from food [Vanover et al 2007a[Vanover et al , 2007b. The high affinity of pimavanserin for 5HT2A receptors [Nordstrom et al 2008] stimulated great interest in its potential for treating PDP.…”
Section: Clinical Trials Of Pimavanserin In Pdpmentioning
confidence: 99%